EFEK ANALGETIK TEPUNG UMBI BIDARA UPAS (Merremia mammosa (Lour) Hall. F.) PADA MENCIT JANTAN - Puspitaningrum, Ika; Kusmita, Lia (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2014)
Abstract Analgesic is a compound that can reduce or eliminate pain without losing consciousness. Bidara upas (Merremia mammosa (Lour) Hall. F.) is one of the flora that part edible tubers and useful for the treatment of, among others, anti-inflammatory and analgesic. The content of flavonoids and alkaloids in the tubers bidara upas could be expected to have an effect as an analgesic. This study aims to determine the analgesic effect bidara upas tuber starch (BUTS) and starch tubers effective dose bidara upas as an analgesic. This study was an experimental study with random sampling technique (random sampling). Testing of analgesic effect (BUTS) using 25 male mice Swiss strain which is divided into 5 groups. Group I, II, and III as a dose of 1, 2 and 3 are a group (BUTS) giving a dose of 1,5; 3; and 6 g/kgBB, IV as a negative control group is a group of distilled water provision, as well as the positive control group V is a group of administration of paracetamol dose 91 mg/kgBB. All treatments are given orally. 5-minute intervals after treatment, all mice were given painful stimuli in the form of a sterile solution of glacial acetic acid 1% v / v with a dose of 300 mg/kgBB and observed stretching that arise every interval of 5 minutes for 60 minutes. Total cumulative stretching all treatment groups were analyzed statistically with SPSS 16 with a 95% confidence level. It also calculated percent analgesic power all treatment groups. The results obtained are significant differences between the groups with a negative control group tuber flour upas bidara three doses. This proves tuber flour bidara upas have analgesic effect. In addition, the results obtained are significant differences between the positive control group by group tuber flour upas bidara three doses. Tuber bidara upas starch total cumulative dose has smaller stretching and % power analgesic greater than the paracetamol group. Based on these results, the effective dose tuber flour bidara upas as analgesic of 1,5 g/kgBB of mice.